The Role of the Indonesian Government in Mitigating Human Trafficking Cases through Social Media - Aprilion, Audi; Murdani, Andika Drajat (Global Local Interactions: Journal of International Relations, 2024)
This study emphasizes the crucial role of the Indonesian government in addressing the emerging issue of human trafficking (TPPO) crimes facilitated by social media, particularly in Cambodia. Due to the swift advancement of information technology, social media has emerged as a viable medium for engaging in the recruitment, promotion, and execution of human trafficking activities. The objective of this study is to enhance comprehension of the Indonesian government's involvement in eliminating TPPO in Cambodia by utilizing social media. This study aims to analyze the measures implemented by the Indonesian government to combat Trafficking in Persons and enhance international collaboration. These measures include the establishment of a Memorandum of Understanding (MoU) between the Indonesian and Cambodian police forces, as well as the signing of bilateral agreements during the Cambodia-Indonesia Bilateral Meetings on Immigration Matters. The analytical findings indicate that the state plays a crucial role in eliminating human trafficking. However, to accomplish the objectives of both nations, it is necessary to engage in bilateral cooperation, namely through partnership with Cambodia.